(3GdeZfj aj GdCfHGA Yf ZQjH GdegPH hGdCSeGAs - (3ESeGYjd Hf gHI Gddg, GHf HGWjSs ((3YHO GdQMef Hf eMehO Hf HNJjGQ Hf YRjR Hf eMeO s)
(3ChdgG (B:s
(3GdMeO ddg eSJMb GdMeO Ydi eQ GdBHGO CeG HYO aEf Chdi eG hbY Hg GdEYJfGA Yde GdePgH ai JCcO GdMGLI Edjg s
(3BNQgG (B:s
(3agPG eG JjSQ gfG GjVGMg hcTa ef GdCSeGA GdJi LGAJ ZjQ eHjfI hde fCd LgOGk ai GdJJHY hGdHMK Je GdcJGH s
(3GdegPH dGHi ESMGb GHQGgje Hf Ydi GdajQhRHGOis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI (B((3dZI (B43) s
Keywords: (3GddZIs